Pengaruh Profitabilitas, Likuiditas, dan Solvabilitas Terhadap Harga Saham dengan EPS sebagai Moderasi - Filia, Zefania Marshanda; Prihatni, Rida; Khairunnisa, Hera (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this study is to determine the effect of profitability, liquidity, and solvency on stock prices with earnings per share as a moderation variable. This research was conducted on energy sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Purposive sampling is used as a sampling technique with 23 selected companies from all energy sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The data in this study was processed using panel data regression analysis with the Eviews 12 program. The results of this study show that liquidity can affect stock prices. While profitability and liquidity have no effect on stock prices. And earnings per share are not able to moderate the effect of profitability, liquidity, and solvency on stock prices. From the results of this study, it is expected to have a good impact on company managers where this information is very important for company managers to attract investors in investing their capital. In addition, it can have an impact on suppliers and creditors for decision making in providing credit for the company. And lastly, it can have an impact on investors as a consideration in making investment decisions.